Effect of the RNF213 p.R4810K Variant on the Progression of Intracranial Artery Stenosis: A 15-Year Follow-up Study. Issue 5 (27th October 2022) - Okazaki, Shuhei; Yoshimoto, Takeshi; Ohara, Mariko; Takagaki, Masatoshi; Nakamura, Hajime; Watanabe, Kotaro; Gon, Yasufumi; Todo, Kenichi; Sasaki, Tsutomu; Araki, Hiroyuki; Yamada, Tomomi; Manabe, Shirou; et al.
Abstract : Background and Objectives: Intracranial artery stenosis is the predominant etiology of ischemic stroke in the Asian population. Furthermore, the presence of the RNF213 p.R4810K variant, which is a susceptibility gene for moyamoya disease, increases the risk of ischemic stroke attributable to large-artery atherosclerosis. Accordingly, we hypothesized that this genetic variant may affect the long-term outcome of intracranial artery stenosis in the East Asian population. We thus aimed to examine the effect of this variant on the long-term progression and prognosis of intracranial artery stenosis. Methods: Using a prospective database, we identified adult patients with intracranial artery stenosis who underwent periodic MRI examinations for >5 years. We evaluated stenosis progression using a validated visual grading system. We excluded patients diagnosed with moyamoya disease at the time of initial MRI. Genotyping of RNF213 p.R4810K was performed at the end of the follow-up period. Results: Among 52 eligible patients, 22 (42%) were carriers of the RNF213 p.R4810K variant. The median follow-up duration was 10.3 years. During the follow-up period, progression of intracranial artery stenosis was observed in 64% variant carriers and 27% noncarriers. There was a significant association of the variant with time to progression of intracranial artery stenosis (hazard ratio [HR] 3.31, 95% CI 1.38–7.90, p = 0.007), and time to the composite endpoint of symptomatic stroke and transient ischemic attack (HR 3.70, 95% CI 1.15–11.86, p = 0.028), but not to symptomatic stroke alone (HR 2.18, 95% CI 0.62–7.74, p = 0.23). Two variant carriers with progression were newly diagnosed with moyamoya disease. Discussion: Our findings indicated that the RNF213 p.R4810K variant increases the risk of intracranial artery stenosis progression.